If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 57 + -8x = 11x Solving 57 + -8x = 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 57 + -8x + -11x = 11x + -11x Combine like terms: -8x + -11x = -19x 57 + -19x = 11x + -11x Combine like terms: 11x + -11x = 0 57 + -19x = 0 Add '-57' to each side of the equation. 57 + -57 + -19x = 0 + -57 Combine like terms: 57 + -57 = 0 0 + -19x = 0 + -57 -19x = 0 + -57 Combine like terms: 0 + -57 = -57 -19x = -57 Divide each side by '-19'. x = 3 Simplifying x = 3
| s^2+10x+16=0 | | x+2(5)=3x+8(2) | | 3+6b=75 | | ac-b=1 | | X^2-2.2x=1.21 | | 5m+-20=27 | | (13w+8)(5w-15)=0 | | 3a+72=75 | | (10+5)+(6x-1)=180 | | (11s+8)(3s-9)=0 | | 33+6b=75 | | 16=8+0.40(x-90) | | 12=8+0.40(x-90) | | 8x-8=10x+6 | | 15+2.00x=15 | | 3ln(5x)=15 | | 3(w-5)=-4w-22 | | -3x-8=-53+2x | | 18=x+(1.15x) | | -8+5w=-18 | | 2(5x+10)=6x-8 | | 2(y-2)-4y=2 | | 2x^2+3x=70 | | 32q-72=0 | | 3b+7a=-5b-62a | | 10+5c-15=-7 | | u^3-4u-24=0 | | 5+x=3x-5 | | N-7=16-2 | | N-7=16-3 | | 64x^2-80x+25y^2= | | 4+5x=-5x+74 |